2022
DOI: 10.1021/acsaem.2c03050
|View full text |Cite
|
Sign up to set email alerts
|

Spent Carbon Cathode Used as a Cathode Material for High-Performance Dual-Ion Batteries: High-Value Utilization

Abstract: Aluminum electrolysis spent cathode carbon (SCC) is one of the high-risk solid waste products in the aluminum electrolysis industry. Generally, harmless storage treatment is used, which fails to achieve high-value utilization. In this study, HCl was used to purify SCC. The purified material showed a richedge structure, expanded layer spacing, and good graphitization. Using SCC as a DIB cathode material and LiTFSI/EC+DMC as an electrolyte, the best electrolyte concentration (6 M) was determined by comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In various studies, the optimal concentration has been observed to fluctuate within the range of 3 M to 6 M [38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…In various studies, the optimal concentration has been observed to fluctuate within the range of 3 M to 6 M [38][39][40].…”
Section: Resultsmentioning
confidence: 99%